Pengembangan Instrumen Penilaian Keterampilan Proses Berbasis Discovery Learning melalui Pembelajaran Daring pada Materi Bioteknologi Konvensional - Sholihah, Fatikhatun Nikmatus; Fadlilah, Laili Rizqi (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the level of validity of the discovery learning-based process skills assessment instrument through online learning on conventional high school level biotechnology materials, namely simple cheese making practicum. This study uses the ADDIE development method. Research and development steps in the Branch model with five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection instrument used was the needs analysis questionnaire method and the validation questionnaire to the assessment instrument experts and material experts. Validation questionnaire was conducted to prove the validity of the developed assessment instrument. The results of the validation of the assessment instrument for the online cheese-making practicum based on the expert validation of the assessment instrument met the